Quantifying spatial dependencies, trade‐offs and uncertainty in bioenergy costs: An Australian case study (1) – least cost production scale. (11th June 2014) - Brinsmead, Thomas S.; Herr, Alexander; O'Connell, Deborah A.
Abstract This paper analyzes costs of several biofuel production pathways in Australia from crop residues (stubble), a lignocellulosic feedstock. As well as land (and sea) transport suitable biofuels, we also consider electricity, and aviation biofuels. Some biofuel cost calculations assume a minimum processing plant scale, often based on contemporary fossil fuels production scales. The more theoretical approach here minimizes production cost by trading off processing and transport costs. Optimal scales and process component costs depend on feedstock spatial concentration; however total costs are less strongly dependent. Lower concentrations correspond to smaller processing plant and greater collection areas and costs. Processing costs are added to feedstock production and transport costs to derive biofuel supply cost ranges as a function of feedstock concentration in an Australian context. Sensitivity analysis then identifies significant parameters and confidence interval estimates. A companion paper generates Australian nationally aggregated supply cost curves. © 2014 Society of Chemical Industry and John Wiley & Sons, Ltd